The Roaring Nineties : A New History of the World's Most Prosperous Decade - Stiglitz, Joseph E. (New York W.W. Norton, 2003)
Challenges perceptions about financial theories stemming from the apparent prosperity of the 1990s, noting such factors as reduced accounting standards and deregulation that caused the economic problems of today.
Include Notes and Index
Keywords: Economic History -- United States -- Economic Conditions -- 1981-2001 -- Globalization -- Business Cycles